INCLUSION OF PEOPLE WITH DISABILITIES AT WORK:: aspects, perspectives and difficulties in the recruitment and selection process - Claro, Thais Cristina; Rodrigues, Lilian Segnini (Revista Interface Tecnológica, 2023)
Law nº 8.213, of 1991, which reserves from 2 to 5% the number of vacancies for Persons with Disabilities (PCD’s) in companies with 100 or more employees, has existed for more than thirty years and has not yet been fully implemented by companies, as well as the true inclusion of PCD in the labor market. The objective of this research is to analyze aspects, perspectives, and difficulties in the process of recruiting and selecting people with disabilities from the perspective of the recruiter. For this, interviews were conducted with recruiters from two different companies, with a semi-structured script. It is concluded that there are still great challenges in the inclusion of these people in the labor market, but the perspectives of those encouraged regarding this inclusion are positive, since companies have tried to comply with Law nº 8.213/1991 and Law nº 13.146 / 2015, which establishes the Statute of Persons with Disabilities.